PREVENTIVE AND DIAGNOSTIC SIGNIFICANCE OF ECG RESULTS IN PATIENTS WITH DIABETES MELLITUS - Avezmetova Sh. J.; Samadova A. B.; Sattorova N. A. (Web of Journals Publishing, 2023)
The scientific article presents the changes in cardiac automatism, conduction and contractility functions and ECG signs in diabetes mellitus. The scientific article is relevant because it highlights the effects of hypoglycemic and hyperglycemic states on the cardiovascular system in patients with diabetes and the types of rhythm disturbances detected in the ECG examination in these cases and their causes.